A case of dengue and COVID-19 co-infection in a young man from Malaysia - Rapai Kasini, Nurul Aisyah; Zainulabid, Ummu Afeera; Safiuddin, Rashida; Meor Jamaludin, Wan Husna Barakah; Kori, Najma; Periyasamy, Petrick (2023)
As Malaysia is highly endemic to both dengue and SARS-CoV-2 infection, it is expected that co-infection can arise. Therefore, we describe a case of a young gentleman with dengue and SARS-CoV-2 co-infection.